Respuesta :

Answer:

[tex]\sf x=7\sqrt{6}[/tex]

Step-by-step explanation:

As the base angles of the triangle are the same, then the legs of the right triangle are also equal.  Therefore, we can use Pythagoras' Theorem to calculate x.

Pythagoras' Theorem:  a² + b² = c²

(where a and b are the legs, and c is the hypotenuse of the right triangle)

Given:

  • a = 7√3
  • b = 7√3
  • c = x

Substituting the given values into the formula:

[tex]\sf \implies (7\sqrt{3})^2+(7\sqrt{3})^2=x^2[/tex]

[tex]\sf \implies147+147=x^2[/tex]

[tex]\sf \implies x^2=294[/tex]

[tex]\sf \implies x=\sqrt{294}[/tex]

[tex]\sf \implies x=\sqrt{49 \cdot 6}[/tex]

[tex]\sf \implies x=\sqrt{49}\sqrt{6}[/tex]

[tex]\sf \implies x=7\sqrt{6}[/tex]

[tex]\\ \rm\Rrightarrow cos\theta=\dfrac{Base}{Hypotenuse}[/tex]

[tex]\\ \rm\Rrightarrow cos45=\dfrac{7\sqrt{3}}{x}[/tex]

[tex]\\ \rm\Rrightarrow \dfrac{1}{\sqrt{2}}=\dfrac{7\sqrt{3}}{x}[/tex]

[tex]\\ \rm\Rrightarrow x=7\sqrt{3}\sqrt{2}[/tex]

[tex]\\ \rm\Rrightarrow x=7\sqrt{6}[/tex]